QT Interval in Pregnant and Non-pregnant Women - Majid Zamani (Emergency, 2014)
Introduction: Prolongation of QT interval might result in dangerous cardiac arrhythmias, including Torsades de Pointes (TdP), consequently leading to syncope or death. A limited number of studies carried out in this respect to date have shown that QT interval might increase during pregnancy. On the other hand, it has been shown that each pregnancy might result in an increase in the risk of cardiac accidents in patients with long QT interval. Therefore, the present study was undertaken to compare QT intervals in pregnant and non-pregnant women. Methods: Pregnant women group consisted of 40 women in the second and third trimesters of pregnancy and the non-pregnant control group consisted of healthy women 18-35 years of age. All the patients underwent standard 12-lead electrocardiogram (ECG). The QT interval was measured for each patient at lead II. The mean corrected QT interval (QTc) and QT dispersions (QTd) were compared between the two groups. Results: Mean heart rates in the pregnant and non-pregnant groups were 98.55±14.09 and 72.53±13.17 beats/minutes (P<0.001). QTd and QTc means were in the normal range in both groups; however, these variables were 49.50±12.80 and 43.03±18.47 milliseconds in the pregnant group and 39.5±9.59 and 40.38±17.20 milliseconds in the control group, respectively (P<0.001). Conclusion: The QT interval was longer in pregnant women compared to non-pregnant women; however, it was in the normal range in both groups. Therefore, it is important to monitor and manage risk factors involved in prolongation of QT interval and prevent concurrence of these factors with pregnancy.